Fixed-Point Results in Fuzzy S-Metric Space with Applications to Fractals and Satellite Web Coupling Problem - Ilyas Khan; Muhammad Shaheryar; Fahim Ud Din; Umar Ishtiaq; Ioan-Lucian Popa (Fractal and Fractional)
In this manuscript, we introduce the concept of fuzzy S-metric spaces and study some of their characteristics. We prove a fixed-point theorem for a self-mapping on a complete fuzzy S-metric space. To illustrate the versatility of our new ideas and related fixed-point theorems, we give examples to illustrate their use in a variety of domains, including fractal formation. These examples illustrate how the fuzzy S-contraction can be applied to iterated function systems, enabling the exploration of fractal forms under diverse contractive conditions. In addition, we solve the satellite web coupling problem by employing this coherent framework.